PENGARUH RISIKO PERUSAHAAN, KUALITAS AUDIT DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2018 - M.Riduan Abdillah; Nurhasanah - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
The purpose of this research is to examine how the influence of company risk, audit quality and audit committee on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. Sampling in this research using purposive sampling method. Data analysis in this research used logistic regression. The results of this research found that company risk has a significant effect on tax avoidance while audit quality and audit committee have no significant effect on tax avoidance.